2017
DOI: 10.1002/jbm.a.36300
|View full text |Cite
|
Sign up to set email alerts
|

Application of kartogenin for musculoskeletal regeneration

Abstract: Kartogenin (KGN) is a recently characterized small molecule that promotes the selective differentiation of mesenchymal stem cells into chondrocytes, and thus, KGN stimulates cartilage regeneration. KGN also possess chondro-protective effect. Furthermore, because it is a highly stable small molecule, KGN can be stored and transported at room temperature. These obvious superiorities over peptide growth factors make KGN a desirable chondrogenic agent for cartilage regeneration. Since its discovery, KGN has drawn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
0
21
1
Order By: Relevance
“…Kartogenin, a small bioactive compound made of 22,000 structurally diverse, heterocyclic small molecules, 2 can promote the differentiation of the stem cells into chondrocytes and enhance cartilage regeneration. 3 However, in the present study, the authors indicated that higher percentages of the fibrocartilage formation were found in the control group than that in the kartogenin-treated group. This result differs from published findings.…”
Section: See Related Article On Page 2579contrasting
confidence: 71%
“…Kartogenin, a small bioactive compound made of 22,000 structurally diverse, heterocyclic small molecules, 2 can promote the differentiation of the stem cells into chondrocytes and enhance cartilage regeneration. 3 However, in the present study, the authors indicated that higher percentages of the fibrocartilage formation were found in the control group than that in the kartogenin-treated group. This result differs from published findings.…”
Section: See Related Article On Page 2579contrasting
confidence: 71%
“…Kartogenin (KGN), a heterocyclic-structured smallmolecule compound, can promote the chondrogenic differentiation of MSCs and protect chondrocytes from ossification (12). The applications of KGN in tissue engineering and regenerative medicine have been widely expanded since its discovery, including musculoskeletal, meniscal, and articular cartilaginous regeneration strategies (13)(14)(15). However, the efficiency of chondrogenesis induced by KGN alone has been far from satisfactory, impeding its further clinical application (16,17).…”
mentioning
confidence: 99%
“…Kartogenin (KGN) is a recently characterized drug with small molecule that promotes the selective differentiation of endogenous MSCs into chondrocytes, thus stimulating cartilage regeneration [10]. In addition, limb skeletal growth and tendon development both can be enhanced by KGN [11,12].…”
Section: Introductionmentioning
confidence: 99%